THE ISSUE OF DEMOCRATIC LEGITIMACY IN MODERN EUROPEAN THEORETICAL DISCOURSE - Вінникова, Н.А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The article examines the issue of legitimacy of decision-making in the framework of global governance. The research focuses on procedure aspects of policy-making in the European Union. Theoretical interpretations of „democratic deficit” are considered in the context related to European Union policy making. It is presented an attempt to recognize factors of legitimization the EU policy decision-making process.